Unraveling the learning behaviors of chinese private college students and effective guiding strategies - Gao, Yanhua; Mohamad, Siti Hajar (Nusantara Journal of Behavioral and Social Science, 2025)
The rapid expansion of private higher education in China has highlighted the need to understand students' learning behaviors and develop effective guidance strategies to enhance academic outcomes. This study examines the learning patterns, motivations, and challenges faced by Chinese private college students using a mixed-methods approach, combining surveys, case studies, and in-depth interviews across multiple institutions. Findings reveal that students’ learning behaviors are influenced by personal goals, institutional support, and family background. While some students demonstrate strong self-regulation and engagement, others struggle with time management, motivation, and active participation. Experiential and project-based learning, academic counseling, and peer mentoring emerge as effective strategies for improving student engagement and academic performance. Institutions that implement blended learning models and real-world applications through industry collaborations show higher levels of student motivation and success. Additionally, fostering a supportive campus culture through extracurricular activities and mentorship programs enhances students' overall learning experience. The study provides practical recommendations for educators and policymakers to optimize instructional methods and institutional resources, ensuring a more effective and inclusive learning environment. By addressing key learning challenges and implementing targeted interventions, private colleges in China can better support students in achieving their academic and career goals.